Development and optimization of a vehicle front-end geometry model for improved pedestrian safety - Abdullah, Kassim Abdulrahman; Venkatason, Kausalyah; Shasthri, Sevaguru; Idres, Moumen; Shah, Qasim Hussain (2014)
In most developed countries, the statistical data of road traffic accidents involving motor vehicle-pedestrian crashes have registered much cause for concern and consequently, a concerted effort by various sectors have for the past two decades been brought to bear towards mitigation efforts. Amongst the different approaches in this direction, it has been established that pedestrian kinematics during impact plays an important role in the ensuing injuries particularly to the head, and has been shown to have a direct bearing with the vehicle front-end shape. This has eventually led to some optimization efforts of the vehicle front-end geometry but due to the complex nature of the problem, many difficulties have been encountered and an exhaustive comprehensive solution has yet to be achieved. In a step towards an attempt in addressing some of these issues, this paper demonstrates the feasibility of an alternative method for developing an optimization friendly deformable vehicle structure, having simple, easily modifiable profile geometry requiring short processing time for the particular purpose of performing multi-parametric optimization of the vehicle front-end shape with the goal of minimizing the sustained head injuries of the pedestrian. A detailed methodology is given on the development of a hybrid vehicle front-end model built with shell elements and a Multi-body plane. The fitness of the method and the case model is assessed by means of comprehensive model validation with respect to the vehicle parts, pedestrian injury criteria as well as the overall kinematics and fall pattern of the pedestrian during impact.